Publisher Correction: Sensory overamplification in layer 5 auditory corticofugal projection neurons following cochlear nerve synaptic damage - Meenakshi M. Asokan (Nature Portfolio, 2018)
In the originally published version of this Article, refs. 54 to 63 were incorrectly cited in the first sentence of the fifth paragraph of the Discussion section. This has now been corrected in both the PDF and HTML versions of the Article.